2015
DOI: 10.1021/acs.joc.5b00049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Five-, Six-, and Seven-Membered 1,3- and 1,4-Heterocyclic Compounds via Intramolecular Hydroalkoxylation/Hydrothioalkoxylation of Alkenols/Thioalkenols

Abstract: Intramolecular hydroalkoxylation/hydrothioalkoxylation of nitrogen-tethered alkenes and alcohols/thiols mediated by boron trifluoride etherate leads to five-membered thiazolidine, six-membered 1,4-oxazines (morpholines) and tetrahydro-2H-1,4-thiazines (thiomorpholines), and seven-membered 1,4-oxazepanes in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…This is further confirmedb yX -ray crystallographic analysis (Figure 1). [14] The reaction was generalized with various alkenols as exemplified in Ta ble 1. It can be seen from Ta ble 1t hat the reactions of alkenols 1a-o,w hich have alkyl-substituted olefinicg roups (entries 1-15), gave tetrahydropyrans 2a-o in good yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further confirmedb yX -ray crystallographic analysis (Figure 1). [14] The reaction was generalized with various alkenols as exemplified in Ta ble 1. It can be seen from Ta ble 1t hat the reactions of alkenols 1a-o,w hich have alkyl-substituted olefinicg roups (entries 1-15), gave tetrahydropyrans 2a-o in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Recently,w ehave developedamethodf or the synthesis of five-, six-, and seven-membered1 ,3-and1 ,4-heterocyclic compounds via intramolecular hydroalkoxylation/hydrothioalkoxylation of alkenols/thioalkenolsm ediated by boron trifluoride etherate. [14] Herein we report am ethodf or the synthesis of tetrahydropyrans and tetrahydrofurans mediated by boron trifluorideetherate.…”
Section: Introductionmentioning
confidence: 99%
“…Saikia's group developed a widely applicable method for the synthesis of morpholines, 1,4‐oxazepanes and thiazolidines . The intramolecular cyclization reaction of (thio)alkenols occurred in good yields (63–92 %) and excellent diastereoselectivity (100 % for the cis analogue), without the need of a transition metal.…”
Section: Synthesis Of Morpholinesmentioning
confidence: 99%
“…69,70 In fact, an exhaustive searching of the literature revealed that very few synthetic approaches for non-fused 1,4-oxazepanes have been reported. [71][72][73] Because of the potential synthetic utility of the γ-aminoalcohols described in Tables 2 and 3 of our previous sections 4 and 5, we envisioned two alternative and straightforward routes for the synthesis of diversely substituted 1,4-oxazepanes 36 via an intramolecular etherification reaction of N-tethered bis-alcohols type 24 and 31 as the key intermediates for these processes. 74 Initially, we planned a three-component Mannich-type reaction/intramolecular etherification sequence under catalyst-free conditions in order to construct the 1,4-oxazepane framework type 36, (Scheme 13).…”
Section: A Straightforward Synthesis Of 47-disubstituted 14-oxazepamentioning
confidence: 99%